Ketahanan Genotipe Kedelai Terhadap Hama Pengisap Polong, Riptortus linearis F. (Hemiptera: Coreidae) - Krisnawati, Ayda; Bayu, Marida Santi Yudha Ika; Adie, dan Mochammad Muchlish (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2019)
The brown stink bug, Riptortus linearis, is the most dominant of soybean pod sucking pest in Indonesia. The objectivesof the study were to identify the resistance of soybean genotypes against brown stink bug and to determine the relationship ofagronomic characters with the intensity of pod and seed damages. Research was conducted at Balitkabi (Malang, Indonesia)from April to August 2018. Thirteen genotypes were assessed for their resistance to brown stink bug under choice and nochoicetests. A randomized block design was carry out with three replicates. The number of punctures on seed, seed and poddamages intensity on no-choice test was higher than those under choice test. Under choice test, the pod damage ranged from19.40-41.68% (average of 29.51%), and the seed damage ranged from 19.31-39.90% (average of 26.80%). Under no-choicetest, the pod damage ranged from 25.77-43.58% (average of 37.41%), and the seed damage ranged from 21.30-58.29%(average of 34.27%). The 11AB and 19BE showed consistently resistant based on pod and seed damage under the choicetest. Under no-choice-test, 19BE showed consistently resistant. The path analysis showed that an increase in the number ofseeds will possibility increase the number of punctures on the seed and then contribute to the increase of yield losses. The19BE which showed consistently resistant to brown stink bug was recommended to be further tested in the adaptation trialand released as superior variety.